A preparation method and application of hot-melt epoxy resin adhesive
Through the preparation method of hot melt epoxy resin binder, composite filler and epoxy resin matrix, and L-glutamic acid and alkylkone dimers are added, the shortcomings of existing binders in corrosion resistance, heat resistance and construction performance are solved, and the excellent corrosion resistance and heat resistance of the binder is achieved, ensuring the durability and safety of road bridges.
Patent Information
- Application Number
- CN202411586621.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The existing adhesives have shortcomings in corrosion resistance, heat resistance and construction performance, making it difficult to ensure the durability and safety of road bridges in complex environments.
By using the hot melt epoxy resin binder preparation method, by combining the composite filler with the epoxy resin matrix, and adding components such as L-glutamic acid and alkylkone dimers, a binder with excellent corrosion resistance and heat resistance is formed.
The excellent corrosion and heat resistance of the adhesive is achieved, and the bonding force can be maintained in complex environments, extend the service life of road bridges and reduce maintenance costs.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and in particular relates to a preparation method of a hot-melt epoxy resin adhesive and application thereof. Background Art
[0002] In the process of modern infrastructure construction and industrial development, adhesives are indispensable key materials. Especially in large-scale engineering fields such as roads and bridges, adhesives play a vital role in ensuring the integrity and stability of the structure. With the increasing traffic flow, increasingly complex environmental conditions, and the continuous improvement of engineering quality and durability requirements, the performance of adhesives directly affects the service life and safety performance of structures such as roads and bridges. Specifically, in the construction of roads and bridges, steel bridge deck pavement faces a complex corrosive environment, and traditional adhesives are often difficult to effectively resist the erosion of corrosive media such as rainwater and industrial pollutants. At the same time, under the high temperature in summer and the frictional heat generated by vehicle driving, the ambient temperature of the adhesive is high. Some adhesives currently on the market are prone to softening and deformation at high temperatures, which reduces the bonding force between the pavement layer and the steel bridge deck, causing bridge deck deformation, displacement and other diseases, and increasing the maintenance cost and safety risks of roads and bridges.
[0003] Therefore, a new method for preparing a binder is provided, which can prepare a binder with good corrosion resistance and heat resistance, thereby overcoming the shortcomings of existing binders in corrosion resistance, heat resistance and construction performance, ensuring the durability and safety of roads and bridges, and meeting the needs of actual engineering construction, which has important practical significance. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a hot-melt epoxy resin adhesive and its application, which solves the problem of poor corrosion resistance and heat resistance of the adhesive in the prior art.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing a hot-melt epoxy resin adhesive, the method comprising the following steps:
[0007] S1. Mix and stir the composite filler and ethanol solution, add 3-(methacryloyloxy)propyltrimethoxysilane and stir magnetically, adjust the pH, add alkyl ketene dimer in a temperature-controlled water bath and stir at a controlled speed, cool and sieve to obtain pretreated material A; mix and stir L-glutamic acid and sodium hydroxide solution to obtain a mixed solution A; add the mixed solution A dropwise to the pretreated material A and ultrasonicate, introduce nitrogen and stir, and after stirring, respectively wash with anhydrous ethanol and deionized water in turn by controlled speed centrifugation, take the product, dry, grind, and pass through a 500-mesh sieve to obtain pretreated material B;
[0008] S2, 2-hydroxyethyl acrylate, n-butyl methacrylate and azobisisobutyronitrile are stirred at a controlled temperature once to obtain a mixture A; epoxy resin, reactive diluent, antioxidant and coupling agent are stirred at a controlled temperature for a second time, added to the mixture A and stirred, and then diglycidyl phthalate is added and stirred, and after the stirring is completed, pretreatment material B is added and stirred for a third time, vacuum degassing is performed to obtain component A; argon gas is introduced, and the curing agent, accelerator and coupling agent are mixed and stirred to obtain component B;
[0009] S3. Mix component A and component B evenly at room temperature to obtain a finished adhesive.
[0010] As a preferred technical solution of the present invention, the composite filler in step S1 includes glass flakes, talcum powder and sericite in a mass ratio of 2-3:2-2.5:1-2.
[0011] Furthermore, the glass flakes have a thickness of 2-3 μm and a flake diameter of 300 mesh, the talcum powder has a mesh size of 3000 mesh, and the sericite has a mesh size of 2500 mesh.
[0012] As a preferred technical solution of the present invention, the mass fraction of the ethanol solution in step S1 is 10%; the concentration of the sodium hydroxide solution is 0.1 mol / L.
[0013] As a preferred technical solution of the present invention, the amount ratio of the composite filler, ethanol solution, 3-(methacryloyloxy)propyltrimethoxysilane and alkyl ketene dimer in step S1 is 20-25g:125-150mL:12-15g:4-6g; the amount ratio of L-glutamic acid and sodium hydroxide solution is 2.5-3g:50-55mL; the mass ratio of the mixed solution A and the pretreated material A is 16-20:5.2-5.5.
[0014] As a preferred technical solution of the present invention, the mixing and stirring time in step S1 is 20-30 minutes; the magnetic stirring time is 30-40 minutes; the pH is adjusted by using 0.1 mol / L sodium hydroxide solution to adjust the pH to 6.0; the temperature of the temperature-controlled water bath is 60-65°C; the speed of the speed-controlled stirring is 7500-8000r / min, and the time is 5-10min; the cooling and sieving are cooling to room temperature and passing through a 100-mesh sieve; the ultrasonic time is 20-30 minutes; the time for stirring by introducing nitrogen is 22-24 hours; the speed of the speed-controlled centrifugal washing is 5000-5500r / min; during the drying, grinding and sieving, the temperature is 50-55°C, and the sieving is passing through a 500-mesh sieve.
[0015] As a preferred technical solution of the present invention, the mass ratio of 2-hydroxyethyl acrylate, n-butyl methacrylate and azobisisobutyronitrile in the mixed material A of step S2 is 3-3.5:3.5-4:0.2-0.5; the mass ratio of the epoxy resin, reactive diluent, antioxidant, coupling agent, mixed material A, diglycidyl phthalate and pretreatment material B in component A is 95-100:10-20:1.5-2:0.5-2:4-6:8-10:10-15; the mass ratio of the curing agent, accelerator and coupling agent in component B is 65-100:4-6:0.5-1.
[0016] Furthermore, the epoxy resin includes any one of bisphenol A epoxy resin E-44 and bisphenol A epoxy resin E-51; the active diluent includes any one of n-butyl glycidyl ether, phenyl glycidyl ether, 1,6-hexanediol diglycidyl ether, 4-tert-butylphenyl glycidyl ether, ethylene glycol diglycidyl ether and resorcinol diglycidyl ether; the antioxidant includes at least one of T501, T502, TBX, BHT and 1010; the coupling agent includes any one of KH-560, KH-550 and KH-570.
[0017] Furthermore, the preparation method of the curing agent comprises: under the protection of inert gas, heating the diamine to 60-95° C., adding the monoepoxide compound dropwise to the diamine at a molar ratio of diamine to monoepoxide compound of 1:2, and stirring for 2-3 hours to obtain the curing agent.
[0018] Furthermore, the diamine includes any one of ethylenediamine, hexamethylenediamine, polyetheramine D230 and polyetheramine D2000; and the monoepoxy compound includes any one of octyl glycidyl ether, versatile glycidyl carbonate and glycidyl methacrylate.
[0019] As a preferred technical solution of the present invention, the temperature of the first temperature-controlled stirring in step S2 is 70-80°C, and the time is 2-2.5h; the temperature of the second temperature-controlled stirring is 60-80°C, and the time is 0.5-1.5h; the time of adding mixed material A and stirring is 2-3h; the time of adding diglycidyl phthalate and stirring is 1-1.5h; the temperature of the third temperature-controlled stirring is 40-45°C, and the time is 2-3h.
[0020] As a preferred technical solution of the present invention, the accelerator in step S2 includes any one of o-cresol, benzyl dimethylamine, N-dihydroaniline, DMP-10, nonylphenol and resorcinol; the coupling agent includes any one of KH-560, KH-550, A-171, KH-570, B201 and Z-6040.
[0021] As a preferred technical solution of the present invention, the mass ratio of component A to component B in step S3 is 1:1-1.5.
[0022] A hot-melt epoxy resin adhesive is used in road and bridge construction.
[0023] Beneficial effects of the present invention:
[0024] (1) The present invention selects glass flakes, talc and sericite as composite fillers, and selects 3-(methacryloyloxy)propyltrimethoxysilane to increase the compatibility and bonding strength of the composite filler with the epoxy resin matrix. Alkyl ketene dimer is then deposited on the composite filler by physical adsorption, so that the product after hydrolysis and desorption of the alkyl ketene dimer provides the composite filler with higher liquid repellency. On this basis, L-glutamic acid is added to produce a strong interfacial interaction with the epoxy group phase in the matrix, thereby helping to further improve the dispersibility of the composite filler. Therefore, the glass flakes, talc and sericite added to the system can synergistically form a maze effect of layers in the system, thereby increasing the penetration distance of the corrosive medium into the substrate, so that the prepared binder product has excellent corrosion resistance.
[0025] (2) The present invention adds n-butyl methacrylate to form a network structure in the system, which improves the heat resistance of the system to a certain extent. At the same time, the addition of diglycidyl phthalate further makes the network structure denser, so the finished adhesive obtained thereby has excellent heat resistance.
[0026] (3) The active diluent selected in the present invention is not easy to volatilize, can participate in the curing reaction, increase the toughness of the curing system, and the selected curing agent can give the cured product better flexibility and elasticity; the present invention is mainly used for steel bridge deck paving in road and bridge construction, and the construction process is simple, and it can be stirred and used at an ambient temperature of 10°C-60°C. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] A method for preparing a hot-melt epoxy resin adhesive, the method comprising the following steps:
[0030] S1. Mix the composite filler and 10% ethanol solution by mass and stir for 20 minutes, add 3-(methacryloyloxy)propyltrimethoxysilane and stir magnetically for 35 minutes, adjust pH to 6.0 with 0.1 mol / L sodium hydroxide solution, add alkyl ketene dimer in a water bath at 60°C and stir at a speed of 7500 r / min for 7.5 minutes, cool to room temperature, and pass through a 100-mesh sieve to obtain pretreated material A; mix L-glutamic acid and 0.1 mol / L sodium hydroxide solution and stir for 30 minutes to obtain a mixed solution A; add the mixed solution A dropwise into the pretreated material A and ultrasonicate for 20 minutes, introduce nitrogen and stir for 22 hours, and after stirring, centrifuge and wash with anhydrous ethanol and deionized water at a speed of 5000 r / min respectively, take the product and dry it at 50°C, grind it, and pass it through a 500-mesh sieve to obtain a pretreated material B;
[0031] The composite filler comprises glass flakes with a thickness of 2 μm and a sheet diameter of 300 mesh, talc powder with a size of 3000 mesh, and sericite with a size of 2500 mesh in a mass ratio of 3:2.5:1;
[0032] The usage ratio of the composite filler, ethanol solution, 3-(methacryloyloxy)propyltrimethoxysilane and alkyl ketene dimer is 25g:125mL:12g:6g;
[0033] The dosage ratio of the L-glutamic acid and the sodium hydroxide solution is 2.5 g:55 mL;
[0034] The mass ratio of the mixed solution A to the pretreated material A is 16:5.2;
[0035] S2, 2-hydroxyethyl acrylate, n-butyl methacrylate and azobisisobutyronitrile were stirred at 70°C for 2.5h to obtain a mixture A; epoxy resin, active diluent, antioxidant and coupling agent were stirred at 60°C for 0.5h, added to the mixture A and stirred for 3h, then diglycidyl phthalate was added and stirred for 1h, and after the stirring was completed, pretreatment material B was added and stirred at 40°C for 2h, vacuum degassing was performed to obtain component A; argon was introduced, and the curing agent, accelerator and coupling agent were mixed and stirred evenly to obtain component B;
[0036] The mass ratio of 2-hydroxyethyl acrylate, n-butyl methacrylate and azobisisobutyronitrile is 3.5:3.5:0.5;
[0037] The mass ratio of the epoxy resin, the active diluent, the antioxidant, the coupling agent, the mixed material A, the diglycidyl phthalate and the pre-treated material B is 95:10:1.75:0.5:4:9:15;
[0038] The epoxy resin includes bisphenol A epoxy resin E-44; the active diluent includes 4-tert-butylphenyl glycidyl ether; the antioxidant includes T501; the coupling agent includes KH-550;
[0039] The preparation method of the curing agent comprises: under the protection of inert gas, heating the diamine to 60° C., adding the monoepoxy compound dropwise to the diamine at a molar ratio of the diamine to the monoepoxy compound of 1:2, and stirring for 2 hours to obtain the curing agent;
[0040] The diamine includes polyetheramine D230; the monoepoxy compound includes tert-butyl glycidyl carbonate;
[0041] S3. Mix component A and component B at a mass ratio of 1:1.5 at room temperature to obtain a finished adhesive.
[0042] Example 2
[0043] A method for preparing a hot-melt epoxy resin adhesive, the method comprising the following steps:
[0044] S1. Mix the composite filler and 10% ethanol solution by mass and stir for 30 minutes, add 3-(methacryloyloxy)propyltrimethoxysilane and stir magnetically for 30 minutes, adjust the pH to 6.0 with 0.1 mol / L sodium hydroxide solution, add alkyl ketene dimer in a water bath at 62.5°C and stir at 8000 r / min for 5 minutes, cool to room temperature, and pass through a 100-mesh sieve to obtain pretreated material A; mix L-glutamic acid and 0.1 mol / L sodium hydroxide solution and stir for 20 minutes to obtain a mixed solution A; add the mixed solution A dropwise into the pretreated material A and ultrasonicate for 25 minutes, introduce nitrogen and stir for 24 hours, and after stirring, centrifuge and wash with anhydrous ethanol and deionized water at 5500 r / min respectively, take the product and dry it at 52.5°C, grind it, and pass it through a 500-mesh sieve to obtain a pretreated material B;
[0045] The composite filler comprises glass flakes with a thickness of 3 μm and a sheet diameter of 300 mesh, talc powder with a size of 3000 mesh, and sericite with a size of 2500 mesh in a mass ratio of 2.5:2.3:1.5;
[0046] The usage ratio of the composite filler, ethanol solution, 3-(methacryloyloxy)propyltrimethoxysilane and alkyl ketene dimer is 22.5 g:137.5 mL:13.5 g:5 g;
[0047] The dosage ratio of the L-glutamic acid and the sodium hydroxide solution is 2.7 g:52.5 mL;
[0048] The mass ratio of the mixed solution A to the pretreated material A is 18:5.3;
[0049] S2, 2-hydroxyethyl acrylate, n-butyl methacrylate and azobisisobutyronitrile were stirred at 75°C for 2 hours to obtain a mixture A; epoxy resin, reactive diluent, antioxidant and coupling agent were stirred at 70°C for 1.5 hours, added to the mixture A and stirred for 2 hours, then diglycidyl phthalate was added and stirred for 1 hour, and after the stirring was completed, pretreatment material B was added and stirred at 45°C for 2.5 hours, and vacuum degassing was performed to obtain component A; argon was introduced, and the curing agent, accelerator and coupling agent were mixed and stirred evenly to obtain component B;
[0050] The mass ratio of 2-hydroxyethyl acrylate, n-butyl methacrylate and azobisisobutyronitrile is 3.25:3.75:0.35;
[0051] The mass ratio of the epoxy resin, the active diluent, the antioxidant, the coupling agent, the mixed material A, the diglycidyl phthalate and the pre-treated material B is 97.5:15:2:2:5:10:12.5;
[0052] The epoxy resin includes bisphenol A epoxy resin E-51; the active diluent includes n-butyl glycidyl ether; the antioxidant includes TBX; the coupling agent includes KH-560;
[0053] The preparation method of the curing agent comprises: under the protection of inert gas, heating the diamine to 95° C., dropping the monoepoxy compound into the diamine at a molar ratio of the diamine to the monoepoxy compound of 1:2, and stirring for 2.5 hours to obtain the curing agent;
[0054] The diamine includes ethylenediamine; the monoepoxide includes octyl glycidyl ether;
[0055] S3. Mix component A and component B at a mass ratio of 1:1.25 at room temperature to obtain a finished adhesive.
[0056] Example 3
[0057] A method for preparing a hot-melt epoxy resin adhesive, the method comprising the following steps:
[0058] S1. Mix the composite filler and 10% ethanol solution by mass and stir for 25 minutes, add 3-(methacryloyloxy)propyltrimethoxysilane and stir magnetically for 40 minutes, adjust pH to 6.0 with 0.1 mol / L sodium hydroxide solution, add alkyl ketene dimer in a water bath at 65°C and stir at a speed of 7750 r / min for 10 minutes, cool to room temperature, and pass through a 100-mesh sieve to obtain pretreated material A; mix L-glutamic acid and 0.1 mol / L sodium hydroxide solution and stir for 25 minutes to obtain a mixed solution A; add the mixed solution A dropwise into the pretreated material A and ultrasonicate for 30 minutes, introduce nitrogen and stir for 23 hours, and after stirring, centrifuge and wash with anhydrous ethanol and deionized water at a speed of 5250 r / min respectively, take the product and dry it at 55°C, grind it, and pass it through a 500-mesh sieve to obtain a pretreated material B;
[0059] The composite filler comprises glass flakes with a thickness of 2.5 μm and a sheet diameter of 300 mesh, talc powder with a size of 3000 mesh, and sericite with a size of 2500 mesh in a mass ratio of 2:2:2;
[0060] The amount ratio of the composite filler, ethanol solution, 3-(methacryloyloxy)propyltrimethoxysilane and alkyl ketene dimer is 20g:150mL:15g:4g;
[0061] The dosage ratio of the L-glutamic acid and the sodium hydroxide solution is 3g:50mL;
[0062] The mass ratio of the mixed solution A to the pretreated material A is 20:5.5;
[0063] S2, 2-hydroxyethyl acrylate, n-butyl methacrylate and azobisisobutyronitrile are stirred at 80°C for 2h to obtain a mixture A; epoxy resin, reactive diluent, antioxidant and coupling agent are stirred at 80°C for 1h, added to the mixture A and stirred for 2.5h, then diglycidyl phthalate is added and stirred for 1.5h, and after stirring, pretreatment material B is added and stirred at 42.5°C for 3h, vacuum degassing is performed to obtain component A; argon is introduced, and the curing agent, accelerator and coupling agent are mixed and stirred evenly to obtain component B;
[0064] The mass ratio of 2-hydroxyethyl acrylate, n-butyl methacrylate and azobisisobutyronitrile is 3:4:0.2;
[0065] The mass ratio of the epoxy resin, the active diluent, the antioxidant, the coupling agent, the mixed material A, the diglycidyl phthalate and the pre-treated material B is 100:20:1.5:1.2:6:8:10;
[0066] The epoxy resin includes bisphenol A epoxy resin E-44; the active diluent includes phenyl glycidyl ether; the antioxidant includes 1010; the coupling agent includes KH-570;
[0067] The preparation method of the curing agent comprises: under the protection of inert gas, heating the diamine to 77.5° C., dropping the monoepoxy compound into the diamine at a molar ratio of diamine to monoepoxy compound of 1:2, and stirring for 3 hours to obtain the curing agent;
[0068] The diamine includes hexamethylenediamine; the monoepoxy compound includes glycidyl methacrylate;
[0069] S3. Mix component A and component B at a mass ratio of 1:1 at room temperature to obtain a finished adhesive.
[0070] Comparative Example 1
[0071] Compared with Example 3, the difference is that glass flakes are not added to the composite filler of Example 1, and talcum powder with half the mass of glass flakes and sericite with half the mass of glass flakes are used instead, and the remaining operating steps and parameters are the same.
[0072] Comparative Example 2
[0073] Compared with Example 3, the difference is that talcum powder is not added to the composite filler of Comparative Example 2, and glass flakes with half the mass of talcum powder and sericite with half the mass of talcum powder are used instead, and the other operating steps and parameters are the same.
[0074] Comparative Example 3
[0075] Compared with Example 3, the difference is that no sericite is added to the composite filler of Example 3, and glass flakes with half the mass of sericite and talcum powder with half the mass of sericite are used instead, and the other operating steps and parameters are the same.
[0076] Comparative Example 4
[0077] Compared with Example 3, the difference is that in step S1 of Comparative Example 4, 3-(methacryloyloxy)propyltrimethoxysilane is not added, and the remaining operating steps and parameters are the same.
[0078] Comparative Example 5
[0079] Compared with Example 3, the difference is that in step S1 of Comparative Example 5, no alkyl ketene dimer is added, and the remaining operation steps and parameters are the same.
[0080] Comparative Example 6
[0081] Compared with Example 3, the difference is that in step S1 of Comparative Example 6, mixed liquid A is not added, and the remaining operation steps and parameters are the same.
[0082] Comparative Example 7
[0083] Compared with Example 3, the difference is that in step S2 of Comparative Example 7, n-butyl methacrylate is not added, and the remaining operating steps and parameters are the same.
[0084] Comparative Example 8
[0085] Compared with Example 3, the difference is that diglycidyl phthalate is not added in step S2 of Comparative Example 8, and the remaining operating steps and parameters are the same.
[0086] Test Example 1
[0087] Test sample preparation: The finished adhesives prepared in Examples 1-3 and Comparative Examples 1-6 were heated and melted and applied on the surface of the PET sheet at a glue application rate of 15 g / m 2 , place another sheet of the same material on the adhesive surface to contact the colloid completely, use a flat press to press and compound, the pressing pressure is 0.5MPa, the pressing time is 5min, and then place it at room temperature until it is completely cured to obtain a test sample;
[0088] Salt spray resistance test: Referring to the test method of ASTM-G85-A5, the test sample was cut into 100mm×100mm specimens and placed in the salt spray resistance test instrument, and the time when powdering, blistering or shedding occurred was recorded. The results are shown in Table 1.
[0089] Table 1
[0090]
[0091] Salt spray resistance is an important indicator for measuring the corrosion performance of materials. It can be seen from Table 1 that the finished adhesive prepared by the present invention has excellent salt spray resistance, that is, the finished adhesive prepared by the present invention has excellent corrosion resistance.
[0092] Test Example 2
[0093] Heat resistance test: Heat the finished adhesives obtained in Examples 1-3 and Comparative Examples 7-8 to 50°C, keep it for 10 minutes, maintain the temperature at 50°C, insert the tube of the glue dispenser into the glue barrel, and then start pneumatic glue dispensing. The test is a 0.5mm diameter copper wire winding coil. First, preheat the coil at 75°C for 30 minutes, then take it out and dispense glue within 5 minutes, dispense glue to the edge of the coil for packaging, and then put it in a 120°C oven for 1.5 hours for curing. After taking it out, it will naturally cool to room temperature. After being placed at room temperature for 24 hours, it will be placed in constant temperature boxes at 80°C, 120°C, and 150°C respectively to see if there is glue flow and deformation of the coil. The test cycle is 1000 hours, and the results are shown in Table 2.
[0094] Table 2
[0095]
[0096] It can be seen from Table 2 that the finished adhesive product prepared by the present invention has excellent heat resistance.
[0097] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0098] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a hot melt epoxy resin adhesive, characterized in that: The preparation method comprises the following steps: S1. Mix and stir the composite filler and ethanol solution, add 3-(methacryloyloxy)propyltrimethoxysilane and stir magnetically, adjust the pH, add alkyl ketene dimer in a temperature-controlled water bath and stir at a controlled speed, cool and sieve to obtain pretreated material A; mix and stir L-glutamic acid and sodium hydroxide solution to obtain a mixed solution A; add the mixed solution A dropwise to the pretreated material A and ultrasonicate, introduce nitrogen and stir, and after stirring, respectively wash with anhydrous ethanol and deionized water in turn by controlled speed centrifugation, take the product, dry, grind, and pass through a 500-mesh sieve to obtain pretreated material B; The composite filler comprises glass flakes, talc and sericite in a mass ratio of 2-3:2-2.5:1-2; the usage ratio of the composite filler, ethanol solution, 3-(methacryloyloxy)propyltrimethoxysilane and alkyl ketene dimer is 20-25g:125-150mL:12-15g:4-6g; the usage ratio of L-glutamic acid and sodium hydroxide solution is 2.5-3g:50-55mL; the mass ratio of the mixed solution A to the pretreated material A is 16-20:5.2-5.5; S2, 2-hydroxyethyl acrylate, n-butyl methacrylate and azobisisobutyronitrile are stirred at a controlled temperature once to obtain a mixture A; epoxy resin, reactive diluent, antioxidant and coupling agent are stirred at a controlled temperature for a second time, added to the mixture A and stirred, and then diglycidyl phthalate is added and stirred, and after the stirring is completed, pretreatment material B is added and stirred for a third time, vacuum degassing is performed to obtain component A; argon gas is introduced, and the curing agent, accelerator and coupling agent are mixed and stirred to obtain component B; The mass ratio of 2-hydroxyethyl acrylate, n-butyl methacrylate and azobisisobutyronitrile in the mixture A is 3-3.5:3.5-4:0.2-0.5; the mass ratio of epoxy resin, reactive diluent, antioxidant, coupling agent, mixture A, diglycidyl phthalate and pretreatment material B in component A is 95-100:10-20:1.5-2:0.5-2:4-6:8-10:10-15; S3. Mix component A and component B evenly at room temperature to obtain a finished adhesive.
2. The method for preparing a hot melt epoxy resin adhesive according to claim 1, characterized in that: The mass ratio of the curing agent, the accelerator and the coupling agent in component B of step S2 is 65-100:4-6:0.5-1.
3. The method for preparing a hot melt epoxy resin adhesive according to claim 1, characterized in that: The epoxy resin includes any one of bisphenol A epoxy resin E-44 and bisphenol A epoxy resin E-51; the active diluent includes any one of n-butyl glycidyl ether, phenyl glycidyl ether, 1,6-hexanediol diglycidyl ether, 4-tert-butylphenyl glycidyl ether, ethylene glycol diglycidyl ether and resorcinol diglycidyl ether; the antioxidant includes at least one of T501, T502, TBX, BHT and 1010; the coupling agent includes any one of KH-560, KH-550 and KH-570.
4. The method for preparing a hot-melt epoxy resin adhesive according to claim 1, characterized in that: The accelerator in step S2 includes any one of o-cresol, benzyl dimethylamine, N-dihydroaniline, DMP-10, nonylphenol and resorcinol; the coupling agent includes any one of KH-560, KH-550, A-171, KH-570, B201 and Z-6040.
5. The method for preparing a hot melt epoxy resin adhesive according to claim 1, characterized in that: In step S3, the mass ratio of component A to component B is 1:1-1.
5.
6. An application of an adhesive prepared by the method for preparing a hot-melt epoxy resin adhesive according to any one of claims 1 to 5, characterized in that: The adhesive is used in road and bridge construction.
Citation Information
Patent Citations
Hot-melt butyl sealant containing alkyl ketene dimer for hollow glass and preparation method of hot-melt butyl sealant
CN106543924A
High-build flexible anti-corrosion epoxy glue and preparation method thereof
CN117327463A